KOMPARASI ATURAN PERSEROAN TERBATAS DALAM UNDANG-UNDANG CIPTA KERJA DAN UNDANG-UNDANG PERSEROAN TERBATAS - Anugrah, Alif Arya; Abraham, Arviedeus Wisnu; Muzizadtullah F., M.Ridwan; Ghifari, Zuhdi Al; Arso, Dimas Dwi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2014)
Our purposes in conducting research in this paper are to find out the comparative substance of the rules regarding Limited Liability Company regulated in the Job Creation Law and the PT Law, and also to find out how the existence or existence of the PT organ structure based on the PT Law in the Job Creation Law which recognizes a new form of company, namely the Individual Company. The research method we use in this paper is normative juridical. From the results of our research, it is found that the substance of the rules that become comparisons include, first, the number of founders of a PT. Second, the authorized capital. And third, how to obtain legal entity status. Furthermore, related to the existence of the structure of PT organs in Law Number 40 of 2007 in the new form of PT, namely the Individual Company regulated in the Job Creation Law has conceptually shifted, namely the GMS organ has conceptually switched to the shareholder organ, and the shareholder organ also doubles as the board of directors held by one person with the elimination of the commissioner organ.